PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA BERBASIS ANIMASI FLASH TOPIK BAHASAN USAHA DAN ENERGI - Arif Rahman Aththibby (Jurnal Pendidikan Fisika, 2015)
The use of computers as a learning medium is increasing. But there is still a bit of educators who use the computer as a medium of education facilities. Based on the research of some experts note that by using animation using flash operated by a computer, student learning outcomes improved. Therefore, it is necessary to develop media-based learning physics flash animation subject and Energy Enterprises are using Macromedia Flash 8. Media are developed based on the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The program was tested by experts in the study of physics and media experts to determine the feasibility media (program) based on predetermined criteria. After the test results obtained through the medium of learning developed worthy to serve as a medium of learning and can be used in learning.